Compensating R&D specialists in Singapore - Chee, Suay Kheong (2014)
In a bid to enhance the nation’s international competitiveness, the Singapore Government has been encouraging companies in the public and private sectors to take up more R&D activities. Besides sufficient funding, the success of R&D projects also depends on the quantity and quality of the personnel involved. The tight labour market and higher career risks associated with R&D work have led to a problem of not attracting enough talented people to take up careers in R&D.